Konsep Bimbingan Konseling Menumbuhkan Kepercayaan Diri (Studi Ayat-Ayat Motivasi Dalam Al-Qur’an Dengan Pendekatan Komunikasi Terapeutik) - Arifin, Isep Zaenal; Wahyudin, Aep; Amaliah, Labibah Inti (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2024)
Islamic counseling plays an essential role in fostering an individual's self-confidence by combining Islamic principles and psychological approaches. This study examines how Quranic verses related to motivation can be applied in counseling to enhance self-confidence, using a therapeutic communication approach. The aim of this study is to demonstrate how Islamic values, such as tawakkul (trust in God), patience, and optimism, can strengthen one's confidence in facing life challenges. Through therapeutic communication based on both spiritual and psychological understanding, counselors can assist individuals in identifying their potential, reducing anxiety, and building stronger intrinsic motivation. Quranic verses teaching the importance of effort and tawakkul provide a profound framework in the counseling process, where individuals are encouraged to believe that every effort made with sincerity and confidence will lead to good results. The findings of this study show that a therapeutic communication approach that integrates Islamic values can significantly enhance an individual's self-confidence and offer practical solutions to psychological issues. Therefore, applying Islamic principles in counseling is highly effective in helping individuals achieve both psychological and spiritual well-being. Keywords: Islamic counseling, self-confidence, Quranic verses, motivation, therapeutic communication